Association of Prepregnancy Obesity versus Excessive Gestational Weight Gain with Adverse Maternal Outcomes in the United States - McLaren, Rodney A., Jr.; Rastogi, Deepa; Rastogi, Shantanu (American Journal of Perinatology, 2025)
Prepregnancy body mass index (BMI) >30 kg/m2 or prepregnancy obesity (PPO) and excessive gestational weight gain (eGWG) are associated with increased risks for adverse maternal outcomes. There is little is known regarding the individual effects of PPO and eGWG. The objective of this study was to compare the effects of PPO and eGWG with adverse maternal outcomes.This was a retrospective cohort study of singleton, live births in the United States in 2018 using data from the National Vital Statistics System. Pregnancies complicated by pregestational diabetes, chronic hypertension, and with unknown maternal BMI were excluded. Institute of Medicine recommendations were used to define gestational weight gain (GWG). These births were divided into four groups: (1) normal prepregnancy BMI and normal GWG, (2) normal prepregnancy BMI and eGWG, (3) PPO and normal GWG, and (4) PPO and eGWG. Outcomes such as gestational diabetes, hypertensive disorders of pregnancy, cesarean delivery, maternal transfusion, and medical intensive care unit admissions were compared among groups using analysis of variance and multivariable logistic regression analysis.Of the 1,432,602 births included in the study, 22.2, 42.3, 10.1, and 25.4% were in Groups 1 to 4, respectively. Compared with pregnancies in Group 1 (adjusted odds ratio [95% confidence interval]), Groups 3 and 4 had higher risk for gestational diabetes (2.80 [2.72–2.88] and 2.28 [2.22–2.34]), respectively, whereas Groups 2 to 4 had higher risk of hypertensive disease of pregnancy (1.58 [1.53–1.64], 3.88 [3.74–4.03], and 5.07 [4.90–5.23]); eclampsia (1.61 [1.33–1.95], 2.99 [2.42–3.69], and 3.57 [2.97–4.29]), and cesarean delivery (1.21 [1.19–1.23], 1.97 [1.92–2.02], and 2.45 [2.40–2.50]), respectively.Both PPO and eGWG are independently associated with higher odds of gestational diabetes, gestational hypertension, preeclampsia, and cesarean sections, with the highest risk among pregnancies with both PPO and eGWG. These data support the importance of prepregnancy weight management in preventing adverse pregnancy outcomes.
Keywords: maternal obesity; prepregnancy obesity; excessive gestational weight gain; maternal outcomes